Human fibrocytic myeloid‐derived suppressor cells express IDO and promote tolerance via Treg‐cell expansion. Issue 11 (18th October 2014) - Zoso, Alessia; Mazza, Emilia M. C.; Bicciato, Silvio; Mandruzzato, Susanna; Bronte, Vincenzo; Serafini, Paolo; Inverardi, Luca
<x xml:space="preserve">Abstract</x> By restraining T‐cell activation and promoting Treg‐cell expansion, myeloid‐derived suppressor cells (MDSCs) and tolerogenic DCs can control self‐reactive and antigraft effector T cells in autoimmunity and transplantation. Their therapeutic use and characterization, however, is limited by their scarce availability in the peripheral blood of tumor‐free donors. In the present study, we describe and characterize a novel population of human myeloid suppressor cells, named fibrocytic MDSC, which are differentiated from umbilical cord blood precursors by 4‐day culture with FDA‐approved cytokines (recombinant human‐GM‐CSF and recombinant human‐G‐CSF). This MDSC subset, characterized by the expression of MDSC‐, DC‐, and fibrocyte‐associated markers, promotes Treg‐cell expansion and induces normoglycemia in a xenogeneic mouse model of Type 1 diabetes. In order to exert their protolerogenic function, fibrocytic MDSCs require direct contact with activated T cells, which leads to the production and secretion of IDO. This new myeloid subset may have an important role in the in vitro and in vivo production of Treg cells for the treatment of autoimmune diseases, and in either the prevention or control of allograft rejection.